Do Childhood Experiences of Parental Separation Lead to Homelessness? - Julie Moschion; Jan van Ours (Tinbergen Institute, 2017)
This paper investigates the effect of parental separation on homelessness. Previous studies are limited in their ability to isolate this effect and can only provide descriptive evidence that parental separations relate to reductions in housing quality and stability. Using a unique dataset of disadvantaged Australians who provide retrospective information on parental separation and homelessness, we estimate bivariate duration models to examine transitions into homelessness resulting from parental separation. Controlling for observed as well as unobserved family and individual characteristics and exploiting the timing of events we investigate whether a causal relationship exists. Our results indicate that parental separation significantly increases the likelihood of experiencing homelessness in subsequent years for boys and girls if the separation occurred before the respondent was 12 years old. Parental separation occurring from the age of 12 only increases boys' likelihood of becoming homeless, but not girls'.
Keywords: D12; J12; 330; Parental separation; Homelessness; Australia